Analysing the interactions of operational issues in sustainable supply chain: a framework. (24th April 2019) - Kumar, Pawan; Kumar, Darshan; Chand, Mahesh
For sustainable management, i.e., environmental, economic and social issues in supply chain, there is an urge need to focus on operational issues. This current research presents a new decision making framework to facilitate this on the basis of questionnaire based survey in Indian industries. Nine operational issues in sustainable supply chain management are considered in this research for analysis. Regarding this, weighted interpretive structural modelling (W-ISM) an extended version of interpretive structural modelling (ISM) has been used to find effectiveness index and to identify the strong and weak areas, to establish a relationship and to identify driving and dependence powers among operational issues in sustainable supply chain management. The results of this analysis are highly beneficial towards society and environment perspectives for industries.